(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Occupational aspirations are the dreams for future occupation unfattered by reality based factors like resources and constraints and adolescence is that stage where these aspirations reach their desired height. The present descriptive survey research conducted on 400 secondary school students (200 males and 200 females) studying in CBSE affiliated schools, is intended to explore the occupational aspirations of secondary school students in relation to their achievement motivation and parental occupation. It was found that majority of the students have moderate levels of occupational aspirations and achievement motivation. Significant positive correlation was found between occupational aspirations and achievement motivation of students whereas parental occupation was not having significant correlation with occupational aspirations of the students. Occupational aspirations of male students were higher than the females while female students were having higher achievement motivation than the males. Suggestions for enhancing level of achievement motivation and shaping the occupational aspirations of students were given by the investigator.